Chloe & Theo - Ord, Monica; Sands, Ezna; Ikummaq, Theo; Johnson, Dakota, 1989-; Springer, Ashley; d ctor.; Sorvino, Mira.; Artica Films (Firm); ARC Entertainment (Firm) ([Place of publication not identified] : [publisher not identified], 2015)
A homeless girl befriends an Inuit who has traveled to New York City from his tiny Arctic hometown with a message for world leaders.
Title from title frame.
Widescreen.
Music, The Newton Brothers ; editor, Jonno Woodford Robinson ; director of photography, Luke Geissbuhler.
Theo Ikummaq, Dakota Johnson, Ashley Springer, Andre De Shields, Mira Sorvino.
DVD, region 1; Dolby digital 5.1.
English dialogue ; Closed-captioned.
Keywords: Homeless girls -- Drama; Inuit -- Travel -- Drama; New York (N.Y.) -- Drama; Feature films; Fiction films; Comedy films; Video recordings for the hearing impaired